(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
The older people need inclusive attention and care equally like any other segment of the population. Like different regions of the world, many Asian countries have already started to pay attention in developing elderly support programs and legal framework. Bangladesh is far behind from many Asian countries in ensuring proper protection and minimum social security services for the senior citizens. At present, the traditional joint family structures have broken down and familial support to the older people have been reduced drastically. Due to absence of proper protective mechanism, millions of older people is living a miserable life within and outside the family. Moreover, community home-based care and residential care facilities has not developed yet in the country. Rather, the concept of old homes, caregivers and rehabilitation centers are getting popular as well. Accordingly, there is no regulatory framework or monitoring authority specifically for old homes and centers. Traditionally it is not much appreciated by the society because of the prevailing social, cultural, and religious norms of the country. Hence, it is the need of time to address the issue of the elderly shelter homes and provide them care in a better way. This study focuses on socio-legal aspects of old homes in Bangladesh and possible recommendations for the betterments of the elderly care delivery. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 119-134